2009
DOI: 10.1080/14786410802242679
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandin vivoeffects of clove on pro-inflammatory cytokines production by macrophages

Abstract: Biological properties of clove have been reported, but little is known about its effect on the immune system. This work was aimed to investigate the effect in vivo of a water-soluble part of hydroalcoholic extract of clove on pro-inflammatory cytokines (IL-1beta and IL-6) production by macrophages of BALB/c mice. The action of the essential oil of clove on the production of these cytokines macrophages was also investigated in vitro. The chemical compositions of the extract and of the oil were also investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…In vivo, treatment with clove/eugenol reduced the ability of mice exposed to thioacetamide (and subsequently undergoing hepatic damage) to produce/release TNF into their systemic circulation (Yogalakshmi et al, 2010). Based on in vitro and in vivo studies of the effects of clove on pro-inflammatory cytokine production by macrophages, Rodrigues et al (2009) claimed eugenol was the causative agent for the particular changes in cytokine formation by cells cultured for 24 h. Those results, like those in the present study, built on evidence from Lee et al (2007) showing that eugenol suppressed production of LPS-induced TNF formation by phagocytes treated in culture for 20 h.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, treatment with clove/eugenol reduced the ability of mice exposed to thioacetamide (and subsequently undergoing hepatic damage) to produce/release TNF into their systemic circulation (Yogalakshmi et al, 2010). Based on in vitro and in vivo studies of the effects of clove on pro-inflammatory cytokine production by macrophages, Rodrigues et al (2009) claimed eugenol was the causative agent for the particular changes in cytokine formation by cells cultured for 24 h. Those results, like those in the present study, built on evidence from Lee et al (2007) showing that eugenol suppressed production of LPS-induced TNF formation by phagocytes treated in culture for 20 h.…”
Section: Discussionmentioning
confidence: 99%
“…While some biologic effects from exposure to clove have been reported (and noted above), apart from the above-noted antiinflammatory effects, effects by clove or key constituents (like eugenol) on specific immune system components/mechanisms have only recently begun to be examined in detail (Bachiega et al, 2012;Grespan et al, 2012;Lee et al, 2007;Rodrigues et al, 2009;Yogalakshmi et al, 2010). As many of those studies have often yielded conflicting results, we undertook a series of studies that would hopefully provide some clarity regarding immunotoxicity/immunomodulatory effects of clove-associated materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that macrophages from various species respond differently to eugenol. Thus, while in our hands unstimulated human mononuclears did not respond to eugenol as for cytokine production, Rodrigues et al [18] have reported that eugenol inhibited the secretion of IL-1β and IL-6 by mouse macrophages. Apparently, Th1 and Th2 cells react adversely to eugenol -while Th1 cytokines TNF-α and IL-2 production by nicotine-induced murine macrophages were down-regulated by eugenol, the generation of Th-2 cytokines IL-10 and TGF-β was activated [19].…”
Section: Discussionmentioning
confidence: 77%
“…[ [96][97][98][99] Eugenol Inhibits IL-1β, TNF and IL-6 release in macrophages. [100,101] Gallic acid Inhibits TNF and IL-6 in HMC-1 cells (10 μM). [102] Gingerol Inhibits IL-1β and IL-12 release in peritoneal macrophages 100 ng/mL) [103] Hydroxytyrosol Inhibits LPS-induced TNF production in THP-1 cells (25, 50 & 100 μM).…”
Section: Lipid Mediator Blockersmentioning
confidence: 99%